Child health consequences of parental opioid use: a scoping review. Issue 4 (2nd October 2021) - Rivera, Rebecca; Engstrom, Malitta; Rees, Jo; Saldana, Lisa; Beidas, Rinad; Marcus, Steven; Rzewinski, Justyna; Lushin, Victor
ABSTRACT: Parental opioid use may negatively affect child health. However, the scope of existing knowledge in this area has not been mapped. We conducted a scoping review of articles (N=1188) describing various influences of parental opioid use on child health. The included studies (N=41) represented three types of such influences: through parental behaviors affected by opioids (n=22), through prenatal opioid exposure (n=9) and through poisoning (n=10). All three types of influences were associated with elevated risks for child health and development. Little research examined implications for child physical health and health service use; however, the existing evidence suggests concerning trends. One question remains largely unanswered, whether children's health is affected directly by parental opioid use or by co-occurring factors such as parental mental health problems and/or environmental risks. Evidence is lacking on best practices to prevent/reduce health risks among children exposed to parental opioid use. Research and policy/practice implications are discussed.